Radioluminescent, thermoluminescent and dosimetric properties of X-ray phosphors - Ignatovych, M.; Kelemen, A.; Otvas, N.; Peto, A.; Ogenko, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Time-resolved radioluminescence (RL) of X-ray phosphors: BaFCl:Eu, ZnS.CdS:Ag and Y₂О₃:Еu, which exhibited ultraviolet (lmax = 390 nm), yellow-green, (lmax = 530 nm) and red (lmax=620 nm) luminescence respectively, have been measured. For tested phosphors a good proportionality between the light output of the radioluminescence and the dose rate in the region of dose rates from 3 to 45 MGy/s has been obtained. It was also revealed that the emitting properties of all phosphors are preserved after high-dose (10⁴ Gy) and high temperature (500°C) annealing the samples. Thermoluminescent (TL) characterization of Sr₃(PO₄)₂:Eu and BaFCl:Eu under X-ray, beta and gamma irradiation have been performed. Linear TL dose dependence under irradiation dose in the mGy - Gy region was revealed, which makes these phosphors suitable also for luminescence dosimetry in the low doses region. Thus, the main characteristics of phosphors: i) the high conversion efficiency, ii) the good dose-rate proportionality, iii) the radiation stability allow to consider these materials as promising for high-energy and high dose rate dosimetry.